Análise crítica do sistema de saída de emergência aplicado no projeto de arquitetura: estudo de caso - Barros, Nayara de (Universidade do Vale do Rio dos Sinos, 2017)
The case study developed in the present work is related to the emergency exit system. It compounds: access to exit, exit itself and the discharge, it can be conceived in various ways, but always aiming at the safety of users and the local community in the face of the challenges facing cities. When anticipating failures of the fire prevention and protection system, the importance of correct planning, development, execution and maintenance of the evacuation project is affirmed. The variables involved in this process and the notions of human behavior in the face of a fire are influenced by people's exit velocity, response time to alarm and reaction due to the smoke. The present work tries to expose the aspects to be analyzed in an evacuation process, linked to emergency exit systems. The analysis in question is a school building of technical education, of medium professional level, that concentrates a population of variable age, including classification of different risks. The project consists of a technical secondary school with a capacity for 1200 students, with blocks separated by function, the administrative / pedagogical block being arranged in two floors, the main object of study. The developed project model is proposed for implementation at the national level, already implemented in the state of Ceará, in 2011. Based on the diagnosis of the use of fire directives, a verification of the application of the project was carried out in the states of Santa Catarina and Rio Grande and the simulation through Pathfinder software to investigate the main variables involved in the evacuation process. Few were the differences noted between the requirements of the regulations. The number of students per classroom was dictated by the law and opinion of the state education systems. A project proposed for the strengthening of national institutions, must pay attention to the fulfillment of the required in the regulations, verifying operation of the project with the help of software. However, a design review is required to meet the minimum required for the effective use of emergency exits.
Keywords: Saída de emergência; Evacuação; Simulação computacional; Comportamento humano; Emergency exit; Evacuation; Computational simulation; Human behavior; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo